Proto-ethnographic publications on the East Slavic theme in the Prague journal «Ost und West» - Lozoviuk, Petr (Journal of the Belarusian State University. History, 2024)
The article analyses the activities of the Prague magazine «Ost und West», founded in 1837, in particular the publication of proto-ethnographic texts on East Slavic subjects. It is noted that the publication sought to mediate cultural exchange between Eastern and Western Europe. The magazine published works by popular Czech and Czech-German authors, as well as translations of the works of famous publicists from Eastern and Western Europe. The work of two authors of the publication, J. G. Kohl and L. Alexander, who surpassed their colleagues in terms of awareness of East Slavic culture and stylistic skill, is studied. At the same time, it briefly tells about the awareness of the German-speaking environment about the life of the Slavic world in the first half of the 19th century, as well as about the attempt of the «Ost und West» magazine to promote Slavic-German rapprochement.
Keywords: journal «Ost und West»; J. G. Kohl; L. Alexander; proto-ethnographic texts; Slavic-German relations